Rancang Bangun Bandpass Filter untuk aplikasi Long Term Evolution (LTE) Frekuensi 1,8 GHz - Teguh Firmansyah; Herudin Herudin; Damar Wardhana (Setrum : Sistem Kendali-Tenaga-elektronika-telekomunikasi-komputer, 2017)
Filter is a device to pass a particular frequency by passing wanted frequency and reduce unwanted frequencies. The frequency that used is depend on the applications used. Based on the frequency regions that are passed, the filter is divideed into several type: Lowpass Filter (LPF), Bandpass Filter (BPF), Highpass Filter (HPF), and Bandstop Filter (BSF). This script was aimed to realized Bandpass Filter (BPF) at frequency 1,8 GHz for long term evolution (LTE). The filter is a hairpin filter, which is one method of designing a distributed element filter with λg/2 length of resonators that is parallel coupled and have resonators topology as ‘U’ shape. Realization of this filters was using microstrip with FR4-Epoxy material as a transmission channel. The information filter performance was measured by using network analyzer. In this BPF designing and realizing, some of the parameters measured are frequency respone, bandwidth, insertion loss, return loss, Voltage Standing Wave Ratio (VSWR). The result of BPF characteristics measurements are: center frequency at 1,8 GHz with 360 MHz bandwidth, insertion loss 8,4 dB, return loss 11,42 dB, VSWR 1,14.